Assessing Delayed Retirement Policies Linked to Dynamic Life Expectancy with Stochastic Dynamic Mortality - Lei He; Tianquan Zhong; Zhenqi Wang (Mathematics, 2023)
The question of how to effectively alleviate the financial pressure on pension insurance due to the increase in life expectancy has become an important issue in the reform of China’s social security system. This paper introduced two life expectancy-related delayed retirement schemes, namely the fixed expected retirement residual life and the fixed life burden ratio. We modeled the financial balance of the employee pension fund and the pension wealth of employees with a dynamic retirement age according to pension policy. Using the population mortality data, the dynamic retirement age under the two schemes was estimated under the stochastic mortality model. Following this, the impact of the two delayed retirement schemes was quantitatively assessed from the perspectives of the financial sustainability of the pension fund and the pension wealth of employees using insurance actuarial methods. This study found that the two life expectancy-related delayed retirement schemes have obvious effects on reducing the gap between the income and expenditure of the pension fund and increasing the pension wealth of employees. Moreover, it found that the fixed expected retirement residual life program contributes more than the fixed life burden ratio program to improve the financial sustainability of the pension fund and the pension wealth benefits of employees.